2004
DOI: 10.1007/s00339-003-2465-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and dynamics of optically excited single-wall carbon nanotubes

Abstract: We have studied the electronic structure and charge-carrier dynamics of individual single-wall carbon nanotubes (SWNTs) and nanotube ropes using optical and electron-spectroscopic techniques. The electronic structure of semiconducting SWNTs in the band-gap region is analyzed using near-infrared absorption spectroscopy. A semi-empirical expression for E S 11 transition energies, based on tight-binding calculations is found to give striking agreement with experimental data. Time-resolved PL from dispersed SWNT-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 40 publications
10
83
0
Order By: Relevance
“…The transients discussed in the following section thus have to be seen in the light of relaxation and repopulation dynamics. In contrast, photoluminescence quantum yields and the dynamics of the associated PL decay generally reflect the population dynamics of the photoluminescent state X [14][15][16]. …”
Section: Interpretation Of Optical Transientsmentioning
confidence: 94%
“…The transients discussed in the following section thus have to be seen in the light of relaxation and repopulation dynamics. In contrast, photoluminescence quantum yields and the dynamics of the associated PL decay generally reflect the population dynamics of the photoluminescent state X [14][15][16]. …”
Section: Interpretation Of Optical Transientsmentioning
confidence: 94%
“…Transient transmission measurements with various pump-photon energies indicated that roughly half of the absorbed 1.6 eV photons excite the small-gap and metallic NTs [17]. Within 0.2 ps, the excited electrons relax to a Fermi-Dirac distribution f T with electronic temperature T [32]. In the schematic of Fig.…”
Section: (D) Figures 2(d) and 2(e)mentioning
confidence: 96%
“…13,14,18,25 These observations have been attributed to a range of dynamic processes including exciton recombination, plasmon relaxation, electron cooling, and radiative relaxation. Differences between isolated [13][14][15][16][17][18] and bundled [17][18][19][20][21][22][23][24] systems could stem from a lack of multitube processes in isolated samples; thus direct comparisons between the two may not be appropriate.…”
Section: Introductionmentioning
confidence: 99%